1997
DOI: 10.3354/meps155269
|View full text |Cite
|
Sign up to set email alerts
|

Role of early post-settlement mortality in recruitment of benthic marine invertebrates

Abstract: Newly settled invertebrates usually are subject to high rates of mortality (Type 111 survivorship). Therefore, knowledge of early post-settlement events is critical in determ~nlng if and when patterns of abundance and distribution of juveniles reflect settlement patterns. Causes of mortality of early juvenile invertebrates include delay of metamorphosis, biological disturbance, physical disturbance and hydrodynamics, physiological stress, predation, and competition. Predation is the best documented cause of ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
411
8
4

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 579 publications
(435 citation statements)
references
References 108 publications
(175 reference statements)
12
411
8
4
Order By: Relevance
“…For example, Evans et al [28] found a negative phenotypic correlation for hatching viability and metamorphic success in the sea urchin Heliocidaris erythrogramma. Post-metamorphic mortality rates of marine invertebrates are notoriously high and can sometimes limit population growth rates [47]. Traditionally, the high mortality rates of larvae and recruits has been attributed to external environmental factors or more recently, the physiological condition of settling larvae [47,48].…”
Section: Discussionmentioning
confidence: 99%
“…For example, Evans et al [28] found a negative phenotypic correlation for hatching viability and metamorphic success in the sea urchin Heliocidaris erythrogramma. Post-metamorphic mortality rates of marine invertebrates are notoriously high and can sometimes limit population growth rates [47]. Traditionally, the high mortality rates of larvae and recruits has been attributed to external environmental factors or more recently, the physiological condition of settling larvae [47,48].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, early post-settlement processes may have a significant role in the regulation of local populations (Hunt and Scheibling, 1997). Young juveniles experience high mortalities, especially due to predation, and as such represent a critical phase in the life-history of the shore crab (Moksnes et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Because C. fornicata and C. peruviana do not move as adults and have only limited mobility as juveniles (and as small males) (Conklin 1897;Chaparro et al 2001a), individuals living at the upper edge of their intertidal range have less time to collect food than their subtidal conspecifics. Unless they have a mechanism that compensates for reduced feeding time, this could potentially limit their vertical distribution, especially if slower growth delays a potential escape in size from mortality in the intertidal zone (Gosselin and Qian 1997;Hunt and Scheibling 1997).…”
Section: Introductionmentioning
confidence: 99%